Barriers and facilitators to primary health care for people with intellectual disabilities and/or autism: an integrative review. Issue 3 (August 2020) - Doherty, Alison Jayne; Randell, Elizabeth; Chauhan, Kerry Hood Umesh; Reed, Janet; Hives, Lucy; Atherton, Helen; James-Jenkinson, Lynn; Taggart, Laurence; Boland, Paul; Leavey, Ralph; Wilson, Neil; Hastings, Richard
No abstract available